Identifying priority value-chains in Ethiopia - Benfica, Rui; Thurlow, James (International Food Policy Research Institute, 2017)
This paper uses an economy-wide model to identify agricultural activities and value-chains in Ethiopia whose expansion would be most effective at generating economic growth, reducing national and rural poverty, creating jobs, and diversifying diets. Results indicate that expanding cereals production would continue to contribute positively to national pro-poor growth. However, the analysis suggests that there is no single value-chain that can achieve all policy objectives. Instead, a more balanced portfolio of valuechains would not only enhance agriculture’s future contribution to poverty reduction and economic growth, but also promote faster rural transformation and dietary diversification, both of which are needed to create job opportunities and improve nutrition outcomes over the longer-term. After considering alternative weighting schemes for competing policy goals, the final analysis suggests that vegetables and fruits/tree crops should be considered “priority” value-chains, because these are among the most effective at achieving multiple policy objectives. Other highly-ranked value-chains include oilseeds, tobacco/cotton/tea, and milk/dairy.